2019
DOI: 10.1007/s42452-019-1673-z
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of transient stability in microgrids using RSFCL with series active power filter

Abstract: Now a day's non-conventional energy sources like PV power and Wind power sources are well developed because conventional energy sources are reduced day by day and at the same time the population has been increased. These drawbacks can be overcome by developing the microgrids. In current trends, microgrid protection is a very challenging task. Due to the interconnection of several distributed generators, fault currents are produced. Resistive type superconducting fault current limiter is used for the protection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…This is why several different SFCL concepts and schemes have been presented and technically proven over the course of the last few decades [11][12][13], typically for use in power transmission and distribution networks. There are numerous common varieties, such as the saturated core [14], transformer [15], reactor [16], flux lock [17], magnetic shield [18], resistive [19,20], and many more.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…This is why several different SFCL concepts and schemes have been presented and technically proven over the course of the last few decades [11][12][13], typically for use in power transmission and distribution networks. There are numerous common varieties, such as the saturated core [14], transformer [15], reactor [16], flux lock [17], magnetic shield [18], resistive [19,20], and many more.…”
Section: Related Workmentioning
confidence: 99%
“…In China, demonstrations of high-voltage SFCL projects have been carried out on grids with voltages ranging from 220 to 500 kilovolts of alternating current (AC) [21], 500 to 160 kilovolts of direct current (DC) [22], and 160 kilovolts of AC [23]. Due to the technical requirements of external grids and the quenching safety concerns of the SFCL, the nominal lasting period for the fault current suppression is often restricted to a few seconds [11][12][13][14][15][16][17][18][19][20][21][22][23]. In light of this, it appears that SFCLs' primary function is to quickly and effectively alleviate the effects of transient fault current.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulation results of this paper show that the combination of suitable RSFCL and ECS can improve the transient stability of power systems better than employing stand-alone ECS. Transient stability improvement in microgrids using RSFCL with a series active power filter has been studied in [17], concluding that RSFCL with seriesactive power filters compensates for the voltage magnitudes and reduces the harmonics and therefore, results in the improvement of the transient stability. In [18], employing a method based on the equal area criterion, selecting the location of RSFCL and inductivetype SFCL (ISFCL) was investigated, taking into account the transient stability issue, and it was concluded that RSFCL is a better choice than ISFCL for improving transient stability power systems.…”
Section: Introductionmentioning
confidence: 99%
“…The injected harmonics can be compensated for with active power filters (APFs) in a precise, rapid and stable manner [5,6]. As a result, these filters have been widely adopted in various industrial sites [7][8][9][10]. Before injecting the harmonic compensation current to the load side, the AFPs must be connected to the grid [11].…”
Section: Introductionmentioning
confidence: 99%